ANALISIS SIFAT FISIKA DAN SIFAT KIMIA GEL BIODIESEL DARI MINYAK BIJI PALEM PUTRI (Adonidia merrillii) - Mahfudhillah, Hamim; Nabihah, Arinza Aulydiana; Choirudin, Hana Haifa; Khuriyah , Siti Imroatul (Jurnal Crystal : Publikasi Penelitian Kimia dan Terapannya, 2024)
Biodiesel is an alkyl ester of long-chain fatty acids, the most common of which are methyl esters or ethyl esters. The manufacturing process involves esterification and transesterification. Traditional sources of biodiesel raw materials such as palm oil, soybeans, and jatropha have been widely studied. The princess palm, widely known as an ornamental plant, produces fruit containing seeds with quite high oil potential. This research aims to produce biodiesel and determine the physical and chemical properties from putri palm seeds. This research is experimental research with a quantitative descriptive approach. Putri palm seed oil is extracted using the soxhletation method with n-hexane solvent. The oil was then esterified using methanol with a catalyst of 1% sulfuric acid with a mole ratio of oil and methanol of 1:8 at a temperature of 60°C for 3 hours. The esterified oil is then transesterified using methanol and KOH with a methanol to oil ratio of 1:20 with KOH of 0.8% for 2 hours at a temperature of 60°C. This research has succeeded in making biodiesel from putri palm seeds. The biodiesel produced is in the form of a gel referred to as biodiesel gel with a yellowish brown color with a density of 1,236 gr/ml and a pour point of 36-38°C. The FFA/ALB value is 0.587%, the acid number is 1.177 mg KOH/g, the IOD number is 34.514 (g-I2/100 g), the saponification number is 63.19 mg KOH/g, the heating value is 48.088 MJ/Kg, and the cetane number 38,620. The IOD number, saponification number, and heating value meet the SNI standards for liquid biodiesel in general, while the cetane number and ALB value are close to SNI standards.